Exploring the Treatment of Nonalcoholic Fatty Liver Disease and Polycystic Ovary Syndrome Based on the Theory of Treating Different Diseases with the Same Method - Zhang, Yue; Ding, Ya; Xia, Xin; Ding, Hui (Journal of Contemporary Medical Practice, 2025)
NAFLD and PCOS represent two common chronic metabolic disorders in modern clinical practice. Epidemiological studies indicate a comorbidity rate reaching 35%-60% [1]. The pathogenesis of both conditions remains incompletely elucidated, with no targeted therapies currently available. Clinical management primarily relies on lifestyle interventions and symptomatic pharmacological treatment. Contemporary research reveals that although these disorders affect different organ systems, they demonstrate significant overlap in both pathological mechanisms and clinical manifestations. IR serves as the common pathological foundation for both diseases. This shared pathogenesis aligns with the traditional Chinese medicine principle of “treating different diseases with the same method,” thereby offering a novel perspective for therapeutic intervention. Through systematic analysis of their pathogenetic similarities and differences, syndrome differentiation characteristics, and corresponding treatment strategies, this study explores the patterns of syndrome differentiation and treatment guided by the holistic concept of traditional Chinese medicine, aiming to provide references for new clinical treatment approaches.